2015
DOI: 10.1177/1557988315585822
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Determinants of Inequality in Smoking Stages: A Distributive Analysis on a Sample of Male High School Students

Abstract: The effect of socioeconomic status on adolescent smoking behaviors is unclear, and sparse studies are available about the potential association. The present study aimed to measure and explain socioeconomic inequality in smoking behavior among a sample of Iranian adolescents. In a cross-sectional survey, a multistage sample of adolescents ( n = 1,064) was recruited from high school students in Zanjan city, northwest of Iran. Principal component analysis was used to measure economic status of adolescents. Concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Several local studies have examined the status of inequality in smoking. One of these evaluated 1064 high school students in Zanjan: the concentration index for regular smoking was -0.10 and the household economic status had the most important role in this inequality (30). A study in Kurdistan reported significant inequality in smoking in 2005 and 2009 (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several local studies have examined the status of inequality in smoking. One of these evaluated 1064 high school students in Zanjan: the concentration index for regular smoking was -0.10 and the household economic status had the most important role in this inequality (30). A study in Kurdistan reported significant inequality in smoking in 2005 and 2009 (21).…”
Section: Discussionmentioning
confidence: 99%
“…In all tests, the significance level was 0.05, and the effect of cluster sampling was considered in calculating the confidence interval by using the "svy" command in Stata software (29). The distribution map of inequality was prepared using ArcGIS software (30).…”
Section: Methodsmentioning
confidence: 99%
“…The findings from the current study also suggest some missing strategies in FCTC, regarding China. Numerous studies have provided evidence for the effectiveness of increasing taxes on tobacco products to promote smoking cessation (Ayubi et al, 2017; Hu et al, 2010; World Health Organization, 2014). Often overlooked is the need to decrease the wide range of cigarette brand prices in China.…”
Section: Discussionmentioning
confidence: 99%
“…on 4,903 students aging 14–19 years in Tabriz, in which the intra-class correlation coefficient was obtained equal to 0.929 from the questions. [ 19 ] Also, according to previous studies,[ 22 23 ] cigarette smoking in three statues of nonsmoker (one who has never smoked even a little), experiment smoker (one who has tried smoking, but at most 100 cigarettes), and regular smoker (daily or on most days of the week) were considered.…”
Section: Methodsmentioning
confidence: 99%